Utilisation of Buffer Management to Build focused productive maintenance - Simatupang, Togar Mangihut (SBM ITB, 2005)
In today’s time based competition, high equipment productivity in a manufacturing line is necessary in ensuring a competitive company. Focused Productive Maintenance emphasizes the importance of achieving profitability through equipment effectiveness. This paper demonstrates the logic of Buffer Management and Focused Productive Maintenance to shape competitive advantage in utilizing resources. Some ideas for future are given.